Efektivitas Layanan Bimbingan Kelompok dengan Teknik Shame Attacking untuk Meningkatkan Self Disclosure SMK N 1 Tanjung Tiram - M. Jawahir Husaini Siagian; Nurussakinah Daulay (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
The purpose of this study was to determine the effectiveness of group guidance services using the Shame Attacking technique in improving students’ self-disclosure. This study employed a quantitative approach with a quasi-experimental research design, specifically a pretest–posttest control group design. The sample consisted of 16 students who were selected through purposive sampling based on low self-disclosure criteria and were then divided into two groups: 8 students in the experimental group and 8 students in the control group. Data were collected using a self-disclosure scale. The instrument applied in this study was an adapted version of the self-disclosure scale used in Tambubolon’s research, which was based on the same theoretical framework as the present study. Data analysis was conducted using the non-parametric Wilcoxon Signed Rank Test with the assistance of SPSS version 27. The hypothesis testing results showed an Asymp. Sig. (2-tailed) value of 0.012, which was lower than the alpha level of 0.05 (0.012 < 0.05). Based on these results, it was concluded that group guidance services using the Shame Attacking technique were effective in improving students’ self-disclosure.